A new solar mid-and-low temperature receiver/reactor with linear Fresnel reflector. (25th May 2023) - Lu, Buchu; Liu, Taixiu; Yan, Xiangyu; Zheng, Zhimei; Liu, Qibin
Highlights: A new solar linear Fresnel hydrogen production system is proposed. Temperature, reaction, and thermal deformation are influenced by solar flux. A porosity of 0.5 gives the maximum methanol conversion rate. Temperature difference is 12.5 % of that in the parabolic trough collector. Abstract: The hydrogen production by a mid-and-low temperature solar receiver/reactor traditionally uses a parabolic trough collector, where the circumferential non-uniformity of the concentrated solar flux poses a challenge to the safety of the catalyst bed and absorber tube. To address this challenge, this study proposes a new hydrogen production method that allows for a more uniform distribution of solar flux, temperature, and deformation in the receiver/reactor by combining a linear Fresnel reflector, a compound parabolic concentrator, a mid-and-low temperature receiver/reactor, and methanol steam reforming reaction. The solar light is concentrated on the surface of the receiver/reactor by the linear Fresnel reflector and the compound parabolic concentrator instead of the traditional parabolic trough collector, and then converted into chemical energy by the methanol steam reforming reaction in the receiver/reactor. A three-dimension model is established to study the performance of the mid-and-low temperature receiver/reactor, including solar flux distribution, fluid flow, mass diffusion, heat transfer, chemical reaction, and structural deformation. The influences of key factors are studied, including the inlet temperature, feeding rate of reactants, molar ratio of water to methanol, and porosity of the catalyst bed. A comparative study between linear Fresnel reflector and parabolic trough collector is conducted to discover the influence of the light-concentrating methods on hydrogen production. The results show that the temperature and reaction fields are highly influenced by the circumferential distribution of the solar flux. The linear Fresnel reflector can achieve a more uniform temperature distribution along the cross-section in the flow direction than the parabolic trough collector owing to the more uniform distribution of solar flux. The maximum temperature difference of the absorber tube in the center of the absorber tube is 12.5 % of that in the parabolic trough collector, which effectively alleviates the local overheating of the catalyst and decreases the thermal deformation of the steel tube. This study provides a reference for the mid-and-low temperature hydrogen production in the linear Fresnel reflector.